Synthesis of Ag2O‐SnO2 and SnO2‐Ag2O Nanocomposites and Investigation on Photocatalytic Performance under Direct Sun Light. Issue 23 (17th June 2020) - Kumar, M. Rajesh; Murugadoss, G.; Venkatesh, N.; Sakthivel, P.
Abstract: Ag2 O‐SnO2 and SnO2 ‐Ag2 O nanocomposites were successfully synthesized by a facile one‐step chemical precipitation method. The microstructural features of nanocomposites were characterized by X‐Ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), high‐resolution transmission electron microscopy (HR‐TEM), Fourier transform infrared spectroscopy (FT‐IR), UV‐visible (UV‐vis) and Photoluminescence (PL) spectroscopy. The SnO2 ‐Ag2 O showed enhanced PL emission than the Ag2 O‐SnO2 nanocomposite. Photocatalytic activity of the nanocomposites was studied for methylene blue (MB) and methyl orange (MO) dyes under sun light. The Ag2 O‐SnO2 nanocomposite showed excellent photocatalytic activity for the degradation of both dyes. The high photocatalytic activity of Ag2 O‐SnO2 could be ascribed to the enhanced charge separation derived from the coupling of Ag2 O with SnO2 due to the potential energy differences between Ag2 O and SnO2, which would promote interfacial charge‐transfer relative to that of charge carrier recombination. Abstract : The photodegradation study performed for methylene blue (MB) and methyl orange (MO) dyes using Ag2 O‐SnO2 and SnO2 ‐Ag2 O catalyst under direct sun irradiation. Comparing the degradation efficiency, Ag2 O/SnO2 nanocomposite was one‐step ahead than SnO2 ‐Ag2 O nanocomposite and also the efficiency reached to 85.3% (MB) and 76.25% (MO) for Ag2 O‐SnO2 nanocomposite within 3 hrs whereas 65.8% (MB) and 58.12% (MO) for SnO2 ‐Ag2 O nanocomposite.